Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst

By using doped porous nanorod-shaped ceria support and ruthenium alloy nanoparticles in ammonia decomposition hydrogen production catalyst, the shortcomings of existing catalysts in low temperature, high activity and high stability are solved, and low-cost and efficient ammonia are achieved Decomposition conversion rate and long-term stability.

CN119186590AActive Publication Date: 2024-12-27XIAMEN UNIV

Patent Information

Application Number
CN202411323378.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The existing ammonia decomposition hydrogen production catalysts have shortcomings in low temperature high activity and high stability, and the high loading of the noble metal ruthenium leads to an increase in costs, limiting its large-scale application.

Method used

Doped porous nanorod-shaped ceria is used as a support, and a catalyst for forming alloy nanoparticles is combined with ruthenium and other metals. Through support synthesis, active component synthesis and in-situ support, an efficient ammonia decomposition hydrogen production catalyst is formed.

Benefits of technology

A low-temperature, high activity and high stability ammonia decomposition catalyst was achieved. The ruthenium load was lower than the existing technology, and the cost advantage was obvious. The ammonia decomposition conversion rate reached 99.5%, and the stable performance was maintained within 1,000 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119186590A_ABST
    Figure CN119186590A_ABST
Patent Text Reader

Abstract

The invention discloses an ammonia decomposition hydrogen production catalyst and a preparation method and application thereof, and relates to the field of catalysis, the catalyst comprises a carrier and an active component, and the carrier is doped porous nanorod-like cerium dioxide; the active component is alloy nanoparticles formed by ruthenium and other metals, and the ruthenium loading amount accounts for 0.8-2% of the total mass of the catalyst. The preparation process of the catalyst comprises the following steps: respectively preparing the carrier and the active component, anchoring the active component on the carrier in a highly dispersed manner in an in-situ loading manner, and enabling the active component of the catalyst and the carrier to form a strong synergistic catalysis effect by using a segmented heating gradient reduction process so as to show the characteristics of low-temperature high activity and high stability. Under the reaction conditions that the normal pressure is 0.1 MPa, the temperature is 450 DEG C and the air speed is 24000mL. G <-1 >. H <-1 >, the ammonia decomposition conversion rate reaches 99.5%, and the catalyst can stably run for 1000h without obvious inactivation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst technology, and in particular to a low-temperature, high-activity, and high-stability ammonia decomposition hydrogen production catalyst, and a preparation method and application thereof. Background Art

[0002] Hydrogen energy has attracted wide attention due to its unique development potential and advantages. Ammonia (NH3) has a high energy density and is easy to store and transport. It is a good hydrogen storage material. Therefore, using ammonia to store and supply hydrogen is one of the development trends of hydrogen energy. Among them, the development of ammonia decomposition and hydrogen production catalysts with superior performance is one of the keys to this process. At present, non-precious metal catalysts represented by nickel-based catalysts are commercially used, but the reaction temperature is generally above 800°C, and the reaction space velocity is often no more than 1000h -1 There is still much room for improvement in the thermal stability of catalysts, energy conservation, emission reduction and efficiency. Precious metal catalysts represented by ruthenium have the characteristics of high activity at low temperatures, but the loading amount of metal ruthenium once exceeded 5wt%. Chinese patent CN117065765A discloses a catalyst for hydrogen production by decomposition of ammonia, with a maximum loading amount of ruthenium reaching 10wt%. In the ammonia decomposition reaction, at 600℃ and 60000h -1 The ammonia decomposition conversion rate reached 99.6% at 500°C and 22,000h. Chinese patent CN113289620A discloses a single-atom ruthenium catalyst with a maximum ruthenium loading of 6wt%. -1 The ammonia decomposition conversion rate reaches 99.8% at a space velocity of 5000 h; Chinese patent CN109529865A discloses a ruthenium-based ammonia decomposition hydrogen production catalyst, the maximum ruthenium loading is 6wt%. In the ammonia decomposition reaction, the ammonia decomposition conversion rate can reach 99.2% at 450°C, but the space velocity is only 5000h -1 The advantages of ruthenium-based catalysts in low temperature and high activity have not been fully exploited, and the high production cost has limited their large-scale use. Therefore, the development of low-temperature, high-efficiency, high-stability and low-cost catalysts is the main direction for the further development of ammonia decomposition hydrogen production technology. Summary of the invention

[0003] The purpose of the present invention is to solve the above problems in the prior art and to provide a low-temperature, high-activity and high-stability ammonia decomposition hydrogen production catalyst and a preparation method and application thereof.

[0004] To this end, the first aspect of the present invention provides a low-temperature, high-activity, and high-stability ammonia decomposition hydrogen production catalyst.

[0005] The catalyst comprises a carrier and an active component. The carrier is a doped porous nanorod-shaped cerium dioxide, and the active component is an alloy nanoparticle formed by ruthenium and other metals.

[0006] Specifically, the carrier selected in the present invention is cerium dioxide. CeO2, as a rare earth oxide, has unique geometric and electronic structural properties, such as Ce 4+ With Ce 3+ During the valence state conversion process, abundant oxygen vacancies are generated. Oxygen vacancies are positively charged, and their electrophilic properties can serve as active sites for the adsorption and activation of many small molecules, thus effectively improving the catalytic activity. At the same time, CeO2 can form a strong interaction with the active components, which helps to adjust their electronic structure and maintain their high dispersion, inhibit their sintering and agglomeration, and improve their stability.

[0007] The use of metal-doped ceria with a porous nanorod-like structure can provide more defect sites and synergistically regulate the electronic structure of the active components, making the dissociation of the reactant NH bonds and the desorption of the products on the surface of the active components more efficient, thereby improving the catalyst performance. On the other hand, the porous nanorod-like ceria with a high specific surface area provides more attachment sites for ruthenium alloy nanoparticles, which not only promotes a more uniform distribution of ruthenium alloy nanoparticles on its surface or near the surface, thereby improving the utilization rate of ruthenium, but also enables a larger number of ammonia molecules to be adsorbed to the catalytic sites, thereby improving the conversion rate of ammonia decomposition.

[0008] The doping element is at least one of magnesium, aluminum, calcium, manganese, yttrium, zirconium and lanthanum.

[0009] The molar ratio of the doping element to cerium dioxide is (0.05-0.5):1.

[0010] The porous nanorod-shaped cerium dioxide has a length of 50-200 nm, a diameter of 10-50 nm, and a specific surface area of ​​100-300 m 2 / g, pore volume 0.10~0.30cm 3 / g, average pore size 5~10nm.

[0011] Specifically, the active component of the present invention is alloy nanoparticles formed by ruthenium and other metals. Compared with ruthenium that is not modified with metals, the added other metals not only have an alloy effect, improve the dispersion of ruthenium, and avoid the agglomeration of ruthenium metal during the reaction, but also optimize the electronic structure of ruthenium, so that it reduces the NH bond cleavage energy barrier on the surface of the active component, increases the adsorption of N atoms and the recombination and desorption of NN, further reduces the reaction temperature, and improves the ammonia decomposition conversion rate.

[0012] The other metal is at least one of iron, cobalt, nickel, copper, zinc, rhodium and iridium.

[0013] The molar ratio of ruthenium to other metals is 1:(0.01~0.1).

[0014] The size of the ruthenium alloy nanoparticles is 0.5-5.0 nm, and the ruthenium accounts for 0.8%-2% of the total mass of the catalyst.

[0015] The second aspect of the present invention provides a method for preparing the above-mentioned ammonia decomposition hydrogen production catalyst.

[0016] The catalyst preparation process includes three parts: carrier synthesis, active component synthesis, and in-situ loading of the active component on the carrier.

[0017] The specific steps include:

[0018] 1. Vector Synthesis

[0019] (1) Weigh a certain proportion of cerium precursor salt, doping element salt, pore expander, and pure water, mix and dissolve. The cerium precursor salt is selected from one of nitrate, sulfate, chloride, or organic ligand salt, preferably including hexahydrated cerium nitrate, tetrahydrated cerium sulfate, heptahydrated cerium chloride, trihydrated cerium chloride, pentahydrated cerium acetate, monohydrated cerium bromide, and acetylacetonate cerium; the doping salt is selected from one of nitrate or chloride of magnesium, aluminum, calcium, manganese, yttrium, zirconium, and lanthanum, preferably including magnesium nitrate, aluminum nitrate, calcium nitrate, manganese nitrate, yttrium nitrate, zirconium nitrate, and lanthanum nitrate; the pore expander is selected from one of dimethylformamide, urea, and hexamethylenetetramine, the molar ratio of the pore expander to the cerium element is (1-10):1, and the molar ratio of pure water to the cerium element is (50-200):1.

[0020] (2) At room temperature, the mixed solution is slowly dripped into a 10-15 mol / L NaOH solution, and after continuing to stir at room temperature for 2-20 hours, the mixture is transferred to a reaction vessel for crystallization reaction.

[0021] Preferably, the molar ratio of NaOH to cerium is (50-200):1; the crystallization temperature is 100-120° C., and the crystallization time is 24-48 hours.

[0022] (3) The product after the crystallization reaction is cooled and allowed to stand for stratification, and the supernatant is replaced with pure water multiple times until the conductivity of the supernatant is ≤50 μS / cm. After centrifugal drying, the powder is ground to obtain a powder, which is then calcined at 600° C. in air atmosphere for 2 h at a heating rate of 5° C. / min to obtain the carrier.

[0023] 2. Synthesis of active ingredients

[0024] A certain proportion of ruthenium precursor salt, other metal salts, NaOH, and reducing agent are weighed and mixed, and vigorously stirred and refluxed at 100-200°C for 10-50h. The product obtained after cooling is the active component. The ruthenium precursor salt is selected from one of ruthenium nitrate, chloride, and organic ligand salt, preferably including ruthenium trichloride hydrate, anhydrous ruthenium chloride, ruthenium acetate, ruthenium oxalate, ruthenium acetylacetonate, triphenylphosphine ruthenium chloride, and carbonyl ruthenium chloride; the other metal salt is selected from one of nitrate, sulfate, and chloride of iron, cobalt, nickel, copper, zinc, rhodium, and iridium, preferably including cobalt nitrate, iron nitrate, nickel nitrate, copper acetate, zinc nitrate, rhodium chloride, and iridium chloride; the reducing agent is one of ethylene glycol, isopropanol, and glycerol; the molar ratio of ruthenium element, NaOH, and reducing agent is 1:(2-10):(500-2000).

[0025] 3. Active components are loaded on the carrier in situ

[0026] Pure water, the carrier prepared above and the active component are mixed in a molar ratio of pure water, cerium element and ruthenium element of (2000-10000):(20-60):1, stirred at 40-100°C for 1-5 hours, then a complexing agent is added, stirred for 1-5 hours, ultrasonicated for 1-3 hours, and allowed to stand for 5-20 hours to complete the in-situ loading of the active component on the carrier.

[0027] The complexing agent is one of citric acid, tartaric acid and oxalic acid, and the molar ratio of the complexing agent to the ruthenium element is (20-100):1.

[0028] The product after standing was centrifugally washed until the conductivity was ≤50μS / cm, and then vacuum dried at 80°C for 10 to 24 hours. Then, in a 10% hydrogen + argon atmosphere, the temperature was increased from room temperature to 200°C at 5°C / min and maintained for 2 hours, then increased to 400°C at 3°C / min and maintained for 2 hours, and then increased to 600°C at 3°C / min and maintained for 2 hours to obtain the above-mentioned ammonia decomposition hydrogen production catalyst.

[0029] During the reduction process, the catalyst undergoes a gradient reduction process with staged temperature increase. The low-temperature stage removes residual moisture in the sample, and the medium- and high-temperature stages fully decompose the pore expander, complexing agent, etc. to form a carrier pore structure, increase its specific surface area, and improve the catalytic active sites. At the same time, the active components are fully reduced to form ultra-small ruthenium nanoparticles that are evenly dispersed on the surface or near the surface of the carrier, so that they are fully combined with the carrier to form a strong mutually coordinated catalytic effect.

[0030] The third aspect of the present invention provides the use of the above-mentioned ammonia decomposition hydrogen production catalyst in the ammonia decomposition hydrogen production reaction.

[0031] Preferably, in a high-purity NH3 atmosphere, the reaction temperature is 300-500°C, and the reaction space velocity is 24000 mL·g -1 ·h -1, the reaction pressure is normal pressure 0.1MPa.

[0032] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:

[0033] (1) The active component of the ammonia decomposition hydrogen production catalyst of the present invention is an alloy nanoparticle formed by ruthenium and other metals. The added other metals can not only improve the dispersion of ruthenium metal, but also synergistically regulate the electronic structure of the catalyst, which helps to improve the activity and stability of the catalyst.

[0034] (2) In the present invention, ruthenium metal accounts for only 0.8% to 2% of the total weight of the catalyst, which is lower than the existing reported technical level and has an advantage in catalyst manufacturing cost.

[0035] (3) The carrier of the ammonia decomposition hydrogen production catalyst of the present invention is a doped porous nanorod-shaped ceria. The addition of doped metals further enriches the defect sites on the surface of ceria, thereby promoting the improvement of the catalyst activity. During the preparation process, the addition of a pore expander enriches the pore structure of the carrier, increases the specific surface area of ​​the carrier, and promotes the uniform distribution of ruthenium alloy nanoparticles on its surface or near the surface, so that the synergistic catalytic advantages of the active sites and the carrier are fully utilized, thereby improving the ammonia decomposition conversion rate and its stability.

[0036] (4) During the preparation of the ammonia decomposition hydrogen production catalyst of the present invention, the active components are in situ loaded on the carrier, and the added complexing agent helps to anchor ruthenium on the surface or near the surface of the carrier, thereby improving the dispersion of ruthenium; the catalyst is subsequently subjected to a gradient reduction process of segmented heating to form an alloy nanoparticle catalyst with moderate size and stable structure.

[0037] (5) The ammonia decomposition catalyst prepared by the present invention has good catalytic performance. When the Ru loading is 1 wt.%, the catalyst can be used for the decomposition of ammonia at 0.1 MPa, 450°C and a space velocity of 24000 mL·g -1 ·h -1 Under the reaction conditions, the ammonia decomposition conversion rate reaches 99.5%, and it can operate stably for 1000h without obvious deactivation. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is the X-ray diffraction pattern of the catalyst of Example 1;

[0039] Figure 2 The low temperature nitrogen adsorption and desorption diagram of the catalysts of Example 1 and Comparative Example 4;

[0040] Figure 3 is a scanning electron microscope image of the catalyst of Example 1;

[0041] Figure 4 is the energy dispersive X-ray spectrum of the catalyst in Example 1;

[0042] Figure 5 This is a 1000h life graph of the ammonia decomposition activity of the catalyst in Example 1;

[0043] Figure 6 The catalyst of Example 1 was heated at a space velocity of 30000 mL·g -1 ·h -1 Activity test;

[0044] Figure 7 This is a transmission electron microscope image of the catalyst in Example 1. DETAILED DESCRIPTION

[0045] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0046] Example 1

[0047] A preparation method and application of a catalyst for hydrogen production by decomposing ammonia, comprising the following process:

[0048] (1) Carrier synthesis: 3.65 g of cerium nitrate hexahydrate, 0.92 g of zirconium nitrate pentahydrate, 4.94 g of dimethylformamide and 21.6 g of pure water were weighed and mixed and dissolved; at room temperature, the above mixture was slowly dripped into a NaOH solution prepared from 45 g of sodium hydroxide and 150 g of pure water; after stirring at room temperature for 2 h, the mixture was transferred to a 500 mL reactor for static crystallization reaction at a crystallization temperature of 120° C. for 48 h; the reaction product was allowed to stand for stratification, and the upper liquid was replaced with pure water several times until the conductivity of the upper clear liquid was ≤50 μS / cm. After centrifugal drying, the powder was ground and then calcined at 600° C. in air atmosphere for 2 h to obtain a carrier.

[0049] (2) Synthesis of active component: Weigh 0.0471 g of ruthenium trichloride hydrate, 0.003 g of cobalt nitrate hexahydrate, 0.058 g of sodium hydroxide, and 21.11 g of ethylene glycol, mix them in a 50 mL round-bottom flask, stir vigorously and reflux at 160° C. for 48 h, and the product obtained after cooling is the active component.

[0050] (3) In-situ loading of active components on the carrier: The carrier and active components prepared above were mixed with 26 g of pure water, stirred at 50°C for 2 h, and then 3.07 g of citric acid was added. The mixture was stirred for 2 h and then ultrasonicated for 1 h. The mixture was allowed to stand for 20 h to complete the in-situ loading of the active components on the carrier.

[0051] (4) The product after standing was centrifuged and washed until the conductivity of the supernatant was ≤50μS / cm, and then vacuum dried at 80℃ for 24h. The catalyst was pressed into tablets, crushed and sieved into 40-80 mesh particles, and a RuCo / CeO2-ZrO2 catalyst with a ruthenium loading of 1% was obtained. 0.1g of the catalyst was weighed and mixed with quartz sand of twice the volume of the same particle size, and filled into a stainless steel fixed bed reactor with an inner diameter of 8mm. The stepwise heating gradient reduction process was used, specifically, the space velocity of 10000mL·g -1 ·h -1 10% H2+Ar reducing gas, 5℃ / min from room temperature to 200℃, keep for 2h, then 3℃ / min to 400℃, keep for 12h, then 3℃ / min to 600℃, keep for 2h. After catalyst reduction treatment, the temperature is naturally lowered to 450℃, keep for 2h, then switch to high-purity ammonia gas preheated at 450℃, and start testing catalyst activity. Catalyst evaluation conditions are reaction temperature 450℃, atmospheric pressure 0.1MPa, 24000mL·g -1 ·h -1 The ammonia decomposition conversion data after the catalytic reaction was run for 48 hours are shown in Table 1.

[0052] Example 2

[0053] A preparation method and application of a catalyst for hydrogen production by decomposing ammonia, comprising the following process:

[0054] (1) Carrier synthesis: 3.65 g of cerium nitrate hexahydrate, 0.56 g of lanthanum nitrate hexahydrate, 4.06 g of urea and 21.6 g of pure water were weighed and mixed and dissolved; at room temperature, the above mixture was slowly dripped into a NaOH solution prepared from 45 g of sodium hydroxide and 150 g of pure water; after stirring at room temperature for 2 h, the mixture was transferred to a 500 mL reactor for static crystallization reaction at a crystallization temperature of 120° C. for 48 h; the reaction product was allowed to stand for stratification, and the upper liquid was replaced with pure water several times until the conductivity of the upper clear liquid was ≤50 μS / cm. After centrifugal drying, the powder was ground and then calcined at 600° C. in air atmosphere for 2 h to obtain a carrier.

[0055] (2) Synthesis of active component: Weigh 0.0471 g of ruthenium trichloride hydrate, 0.003 g of iridium trichloride hydrate, 0.058 g of sodium hydroxide, and 31.33 g of propylene glycol into a 50 mL round-bottom flask, stir vigorously and reflux at 160° C. for 48 h, and the product obtained after cooling is the active component.

[0056] (3) In-situ loading of active components on the carrier: The carrier and active components prepared above were mixed with 26 g of pure water, stirred at 50°C for 2 h, and then 1.44 g of oxalic acid was added. The mixture was stirred for 2 h and then ultrasonicated for 1 h. The mixture was allowed to stand for 20 h to complete the in-situ loading of the active components on the carrier.

[0057] (4) The product after standing was centrifuged and washed until the conductivity of the supernatant was ≤50μS / cm, and then vacuum dried at 80℃ for 24h. The catalyst was pressed into tablets, crushed and sieved into 40-80 mesh particles, and a RuIr / CeO2-La2O3 catalyst with a ruthenium loading of 1% was obtained. 0.1g of the catalyst was weighed and mixed with quartz sand of twice the volume of the same particle size, and filled into a stainless steel fixed bed reactor with an inner diameter of 8mm. The stepwise heating gradient reduction process was used, specifically, the space velocity of 10000mL·g -1 ·h -1 10% H2+Ar reducing gas, 5℃ / min from room temperature to 200℃, keep for 2h, then 3℃ / min to 400℃, keep for 12h, then 3℃ / min to 600℃, keep for 2h. After catalyst reduction treatment, the temperature is naturally lowered to 450℃, keep for 2h, then switch to high-purity ammonia gas preheated at 450℃, and start testing catalyst activity. Catalyst evaluation conditions are reaction temperature 450℃, atmospheric pressure 0.1MPa, 24000mL·g -1 ·h -1 The ammonia decomposition conversion data after the catalytic reaction was run for 48 hours are shown in Table 1.

[0058] Example 3

[0059] A preparation method and application of a catalyst for hydrogen production by decomposing ammonia, comprising the following process:

[0060] (1) Carrier synthesis: 3.85 g of cerium nitrate hexahydrate, 1.22 g of magnesium nitrate hexahydrate, 9.47 g of hexamethylenetetramine, and 21.6 g of pure water were weighed and mixed and dissolved; at room temperature, the above mixture was slowly dripped into a NaOH solution prepared from 45 g of sodium hydroxide and 150 g of pure water; after stirring at room temperature for 2 h, the mixture was transferred to a 500 mL reactor for static crystallization reaction at a crystallization temperature of 120° C. for 48 h; the reaction product was allowed to stand for stratification, and the upper liquid was replaced with pure water several times until the conductivity of the upper clear liquid was ≤50 μS / cm. After centrifugal drying, the powder was ground and then calcined at 600° C. in air atmosphere for 2 h to obtain a carrier.

[0061] (2) Synthesis of active component: Weigh 0.0471 g of ruthenium trichloride hydrate, 0.004 g of nickel nitrate hexahydrate, 0.058 g of sodium hydroxide, and 20.45 g of isopropanol, mix them in a 50 mL round-bottom flask, stir vigorously and reflux at 160° C. for 48 h, and the product obtained after cooling is the active component.

[0062] (3) In-situ loading of active components on the carrier: The carrier and active components prepared above were mixed with 26 g of pure water, stirred at 50°C for 2 h, and then 2.4 g of tartaric acid was added. The mixture was stirred for 2 h and then ultrasonicated for 1 h. The mixture was allowed to stand for 20 h to complete the in-situ loading of the active components on the carrier.

[0063] (4) The product after standing was centrifuged and washed until the conductivity of the supernatant was ≤50μS / cm, and then vacuum dried at 80℃ for 24h. The catalyst was pressed into tablets, crushed and sieved into 40-80 mesh particles, and a RuNi / CeO2-MgO catalyst with a ruthenium loading of 1% was obtained. 0.1g of the catalyst was weighed and mixed with quartz sand of twice the volume of the same particle size, and filled into a stainless steel fixed bed reactor with an inner diameter of 8mm. The stepwise heating gradient reduction process was used, specifically, the space velocity of 10000mL·g -1 ·h -1 10% H2+Ar reducing gas, 5℃ / min from room temperature to 200℃, keep for 2h, then 3℃ / min to 400℃, keep for 12h, then 3℃ / min to 600℃, keep for 2h. After catalyst reduction treatment, the temperature is naturally lowered to 450℃, keep for 2h, then switch to high-purity ammonia gas preheated at 450℃, and start testing catalyst activity. Catalyst evaluation conditions are reaction temperature 450℃, atmospheric pressure 0.1MPa, 24000mL·g -1 ·h -1 The ammonia decomposition conversion data after the catalytic reaction was run for 48 hours are shown in Table 1.

[0064] Comparative Example 1

[0065] The only difference between Comparative Example 1 and Example 1 is that, during the carrier synthesis process in step (1), zirconium nitrate pentahydrate was not added.

[0066] Comparative Example 2

[0067] The only difference between Comparative Example 2 and Example 1 is that, during the synthesis of the active component in step (2), cobalt nitrate hexahydrate was not added.

[0068] Comparative Example 3

[0069] The only difference between Comparative Example 3 and Example 1 is that in step (3), citric acid is not added, that is, the carrier and the active component are not loaded in situ, but the active component is simply impregnated on the carrier.

[0070] Comparative Example 4

[0071] The only difference between Comparative Example 4 and Example 1 is that no dimethylformamide was added during the carrier synthesis process in step (1).

[0072] Comparative Example 5

[0073] The only difference between Comparative Example 5 and Example 1 is that the temperature is directly raised to 600° C. at 5° C. / min for 2 h under the same reducing atmosphere without undergoing the gradient reduction process of staged heating.

[0074] Table 1

[0075] sample Ammonia decomposition conversion rate (%) Example 1 99.5 Example 2 99.1 Example 3 99.4 Comparative Example 1 93.2 Comparative Example 2 91.8 Comparative Example 3 80.6 Comparative Example 4 89.1 Comparative Example 5 93.6

[0076] As shown in Table 1, the catalyst for hydrogen production from ammonia decomposition prepared in Example 1 has a reaction temperature of 450°C, a normal pressure of 0.1 MPa, and a reaction space velocity of 24000 mL·g -1 ·h -1 After 48h of reaction time, the conversion rate reached 99.5%, which has excellent ammonia decomposition catalytic performance.

[0077] Figure 1 This is the X-ray diffraction diagram of Example 1. It can be seen from the figure that only the characteristic diffraction peak of CeO2 appears in the sample, and there is no diffraction signal of Zr species and RuCo alloy. This is because Zr is embedded in the CeO2 lattice, and the formed RuCo alloy nanoparticles are highly dispersed, with small particle size and low content.

[0078] Figure 2 The low temperature nitrogen absorption and desorption diagram of the catalysts of Example 1 and Comparative Example 4 is shown in the figure. It can be seen from the figure that in Example 1, the pore-enlarging agent dimethylformamide is added, and its specific surface area and pore volume are larger, which are 200.6m 2 / g and 0.30cm 3 / g, the isothermal adsorption-desorption curve is type IV, with a mesoporous structure and an average pore size of 9.1nm. Comparative Example 4 did not add dimethylformamide, and its specific surface area was 167.6m 2 / g, pore volume is 0.27cm 3 / g, average pore size 8.2nm.

[0079] Figure 3 This is a scanning electron microscope image of the catalyst of Example 1. It can be seen from the figure that the catalyst has a distinct nanorod-like structure, which is conducive to the active components being anchored on the surface or near the surface of the carrier to form a strong interaction. The scale in the figure is located in the lower left corner and is 20nm. In contrast, the length of the porous nanorod-like cerium dioxide is distributed in the range of 50 to 200nm, with an average length of 150nm, and the diameter is distributed in the range of 10 to 50nm, with an average diameter of 18nm.

[0080] Figure 4 This is the energy dispersive X-ray spectrum of the catalyst of Example 1. It can be seen from the figure that the RuCo nano alloy particles formed by the catalyst are distributed on the surface of the carrier CeO2, which can inhibit the sintering and agglomeration of ruthenium.

[0081] Figure 5The 1000h life graph of the catalyst ammonia decomposition activity of Example 1 shows that the catalyst has a high activity at atmospheric pressure of 0.1 MPa, 450°C and a space velocity of 24000 mL·g -1 ·h -1 Under the reaction conditions, the ammonia decomposition conversion rate reaches 99.5%, and it can run stably for 1000h without obvious deactivation, with excellent thermal catalytic ammonia decomposition performance.

[0082] Changing the reaction conditions, the space velocity was increased from 24000 mL·g -1 ·h -1 Adjust to 30000mL·g -1 ·h -1 , see Figure 6 The ammonia decomposition conversion rate reached 93.1%, and it was able to run stably for 100 hours without obvious deactivation. At higher space speeds, the performance was still excellent.

[0083] Figure 7 This is a transmission electron microscope image of the catalyst of Example 1. It can be seen from the image that the size of the formed RuCo nano alloy particles is about 3.0 nm.

[0084] It can be seen from the reaction data of Example 1 and Comparative Example 1 that in Comparative Example 1, since zirconium nitrate pentahydrate was not added during the synthesis of the carrier, the defect sites on the carrier surface could not be further enriched and the electronic structure of the active component could not be optimized, resulting in a decrease in catalytic performance.

[0085] It can be seen from the reaction data of Example 1 and Comparative Example 2 that since cobalt nitrate hexahydrate was not added in Comparative Example 2, alloy nanoparticles cannot be formed with ruthenium, resulting in partial agglomeration of ruthenium during the long reaction process and a decrease in dispersion, which leads to a significant decrease in catalytic performance.

[0086] It can be seen from the reaction data of Example 1 and Comparative Example 3 that in Comparative Example 3, since no chelating agent citric acid is added, the active components are unevenly distributed on the carrier, and the size of the ruthenium cobalt alloy nanoparticles after reduction is large, resulting in a significant decrease in the conversion rate. In Example 1 where a chelating agent is added, the carrier and the active metal are in a highly dispersed slurry state, so that the active components loaded in situ are more conducive to combining with the surface or near-surface of the carrier to form highly dispersed, small-sized ruthenium cobalt alloy nanoparticles. Therefore, the activity of the prepared catalyst can be effectively improved.

[0087] It can be seen from the reaction data of Example 1 and Comparative Example 4 that in Comparative Example 4, since the pore-expanding agent dimethylformamide was not added during the carrier synthesis process, the carrier failed to effectively form a porous structure and a high specific surface area, affecting the loading of the active components and resulting in reduced catalyst activity.

[0088] It can be seen from the reaction data of Example 1 and Comparative Example 5 that in the catalyst that has not been treated by the gradient reduction process with segmented heating, ruthenium may undergo high-temperature sintering and agglomeration, which is not conducive to the formation of a metal-oxide structure with moderate size and stable structure, resulting in catalytic activity that is inferior to that of Example 1.

Claims

1. A method for preparing a catalyst for hydrogen production by decomposing ammonia, characterized in that: The following steps are involved: 1) Carrier synthesis: The cerium precursor salt, doping salt, pore expander and water are mixed and dissolved, and then dripped into a NaOH solution, stirred and transferred to a hydrothermal reactor for constant temperature crystallization. The crystallized product is washed with water and alcohol to a certain conductivity, centrifuged, dried and calcined at high temperature to obtain a carrier; 2) Synthesis of active components: After the ruthenium precursor salt, other metal salts, NaOH, reducing agent and water are mixed and dissolved, the mixture is stirred and refluxed at a constant temperature, and the product obtained after cooling is the active component; 3) Active components are loaded on the carrier in situ: water, carrier and active components are mixed and stirred, a complexing agent is added, and then ultrasonic, stirred and allowed to stand to complete the in-situ loading of the active components on the carrier; 4) Gradient reduction by staged heating: the product is centrifugally washed, vacuum dried, and staged heated and reduced to obtain the ammonia decomposition hydrogen production catalyst.

2. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In step 1), the cerium precursor salt is selected from one of nitrates, sulfates, chlorides or organic ligand salts, and the doping salt is selected from one of nitrates or chlorides of magnesium, aluminum, calcium, manganese, yttrium, zirconium or lanthanum; the pore expander is selected from one of dimethylformamide, urea and hexamethylenetetramine, and the molar ratio of the pore expander to the cerium precursor salt is (1-10):1; the crystallization temperature is 100-120°C, and the crystallization time is 24-48h; the high temperature calcination temperature is 500-800°C, and the calcination time is 2-6h.

3. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In step 2), the ruthenium precursor salt is selected from one of ruthenium nitrate, chloride, and organic ligand salts, and the other metal salts are selected from one of iron, cobalt, nickel, copper, zinc, rhodium, and iridium nitrate, sulfate, and chloride; the reducing agent is selected from one of ethylene glycol, isopropanol, and glycerol, and the molar ratio of the reducing agent to the ruthenium precursor salt is (500-2000):1; the stirring reflux temperature is 100-200°C, and the time is 10-50h.

4. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In step 3), the complexing agent is one of citric acid, tartaric acid and oxalic acid, and the molar ratio of the complexing agent to the active component is (20-100):1; the molar ratio of the carrier to the active component is (20-60):

1.

5. The method for preparing a catalyst for hydrogen production by decomposing ammonia according to claim 1, characterized in that: In step 4), the temperature-raising reducing atmosphere is one of hydrogen, a hydrogen and argon mixer, and a hydrogen and helium mixture, and the temperature is raised from room temperature to 100-200° C. and maintained for 1-5 hours, then raised to 300-400° C. and maintained for 1-5 hours, and then raised to 500-600° C. and maintained for 1-5 hours.

6. A catalyst for hydrogen production by decomposing ammonia, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

7. The catalyst for hydrogen production by decomposing ammonia according to claim 6, characterized in that: The catalyst comprises a carrier and an active component, wherein the carrier is a doped porous nanorod-shaped cerium dioxide, and the molar ratio of the doping element to the cerium dioxide is (0.05-0.5):1; the active component is an alloy nanoparticle formed by ruthenium and other metals, ruthenium accounts for 0.8%-2% of the total mass of the catalyst, and the molar ratio of ruthenium to the other metals is 1:(0.01-0.1).

8. The catalyst for hydrogen production by decomposing ammonia according to claim 7, characterized in that: The porous nanorod-shaped cerium dioxide has a length of 50 to 200 nm, a diameter of 10 to 50 nm, and a catalyst specific surface area of ​​100 to 300 m 2 / g, pore volume is 0.10~0.30cm 3 / g, the average pore diameter is 5-10nm, and the size of the alloy nanoparticles is 0.5-5.0nm.

9. Use of the catalyst prepared by any preparation method of claims 1 to 5 or the catalyst according to any one of claims 6 to 8, characterized in that: Used for thermal catalytic ammonia decomposition to produce hydrogen.

10. The use according to claim 9, characterized in that The reaction parameters are as follows: in NH3 atmosphere, reaction temperature 300-500°C, reaction space velocity 10000-50000 mL·g -1 ·h -1 , the reaction pressure is normal pressure 0.1MPa.

Citation Information

Patent Citations

  • Catalyst system for preparing acrylics through acetylene carbonylation as well as preparation and application of catalyst system

    CN114425367A

  • Catalyst for hydrogen production through ammonia decomposition as well as preparation method and application of catalyst

    CN117960221A

  • Catalyst for ammonia decomposition, process for producing the same, and method for treating ammonia

    JP2010094668A

Cited By

  • Rod-like rare-earth metal oxide ruthenium-loaded catalyst for efficient ammonolysis hydrogen production and preparation method of rod-like rare-earth metal oxide ruthenium-loaded catalyst

    CN119793454A

  • XM% Co / CemLa1-mO2-delta catalyst for hydrogen production through water decomposition and preparation method of xM% Co / CemLa1-mO2-delta catalyst

    CN121669247A

  • Preparation method of nickel-based catalyst based on expanded graphite dispersion and application of nickel-based catalyst in hydrogen production through ammonia cracking

    CN121945084A